Unlocking the Potential for Creative Thinking Ability and Self-Efficacy: Implementation of Numbered Head Together and Algebra Blocks in Middle School Students - Listiasari, Dwi; Nasrullah, Anton; Yendra, Novi; Rahmadani, Kurniati; Egwuasi, Princewill Ikechukwu (International Journal of Mathematics and Mathematics Education (IJMME), 2023)
This study examines how algebra block support and the Numbered Head Together (NHT) learning paradigm affect secondary school students' mathematical creativity and self-efficacy. The literature review highlights the necessity of creative teaching strategies in mathematics education. In this study, a non-equivalent control group was utilized in a controlled experimental design, with one group implementing the NHT model with algebra block support and another group employing traditional teaching techniques. Pretest, posttest, and self-efficacy instruments were used to gather data. The study's results indicated a significant increase in students' mathematical creativity capacity when utilizing algebra blocks to support the NHT model. In addition, there was a noticeable increase in the pupils' self-efficacy. An examination of the data using statistical methods revealed notable distinctions between the experimental and control groups. The primary finding indicates that the NHT learning paradigm, in conjunction with algebra blocks, helps enhance secondary school students' mathematical creativity and self-efficacy capacity. The study's findings offer insightful information about initiatives to enhance methods for teaching mathematics.